Pajak Daerah, Retribusi Daerah, dan Pengelolaan Kekayaan Daerah Terhadap Pendapatan Asli Daerah di Indonesia - Lilis Setyowati (BADAN PENERBIT STIEPARI PRESS, 2021)
This study aims to determine the effect of local taxes , local retributions, results of separated regional wealth management on local revenue in all regions in Indonesia for the 2020 period. The sampling technique used in this study is using the purposive sampling method. The total sample is 374 local governments throughout Indonesia. This study uses secondary data obtained from budget realization on the website www.djpk.kemenkeu.go.id. The method of data analysis uses multiple linear regression using SPSS version 25. The results obtained from this study indicate that: local taxes have an effect on local revenue, local retributions have an effect on local revenue, and result of separated regional wealth management has an effect on local revenue.